2012
DOI: 10.1021/ef300393h
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Fuels for Spark-Ignition Engines: Mixing Rules for the Laminar Burning Velocity of Gasoline–Alcohol Blends

Abstract: Experimental measurements of the laminar burning velocity are mostly limited in pressure and temperature and can be compromised by the effects of flame stretch and instabilities. Computationally, these effects can be avoided by calculating one-dimensional, planar adiabatic flames using chemical oxidation mechanisms. Chemical kinetic models are often large, complex and take a lot of computation time, and few models exist for multi-component fuels. The aim of the present study is to investigate if simple mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Sileghem et al [16,17] investigated the laminar burning velocity of alcohol-hydrocarbon blends. Methanol has the highest laminar burning velocity followed by ethanol and gasoline.…”
Section: Iso-stoichiometric Ternary Blendsmentioning
confidence: 99%
“…Sileghem et al [16,17] investigated the laminar burning velocity of alcohol-hydrocarbon blends. Methanol has the highest laminar burning velocity followed by ethanol and gasoline.…”
Section: Iso-stoichiometric Ternary Blendsmentioning
confidence: 99%
“…Similar to the mixing rules for laminar burning velocity of methanol-gasoline blends, the energy fraction mixing rule has the best agreement [26,27].…”
Section: Autoignition Correlation For Alcohol-blendsmentioning
confidence: 63%
“…In [46], Sileghem et al demonstrated that a mixing rule applied to the components of a TRF surrogate can be used to predict the LFS of a commercial gasoline over a given temperature range. In [48], the same authors investigated the capability of simple mixing rules, applied to ETRF components, to predict LFS of gasoline-ethanol blends. The results proved that simple mixing rules taking into account only the ethanol-hydrocarbon blend composition are sufficiently accurate to predict s L .…”
Section: Gasoline-ethanol Fuel Surrogate Formulationmentioning
confidence: 99%
“…where n is the number of the blend components. As stated earlier, many other mixing rules (even more complex) are available in literature [48,49,50]. All can be used in the methodology proposed in the present work, if analytical equations are based on the pure component concentrations, as Eq.…”
Section: Gasoline-ethanol Fuel Surrogate Formulationmentioning
confidence: 99%